Pengaruh Orientasi Arah Serat Terhadap Kekuatan Mekanis Komposit Serat Pandan Dengan Pelapisan Carbon Cloth - Ferdinan Ashada; Sehono Sehono; Dhimas Wicaksono (Journal of Metallurgical Engineering and Processing Technology, 2023)
Indonesia has a wealth of natural resources that are very abundant, where one of the natural resources that can be found in Indonesia is plants that contain fiber. At this time plants containing fiber were mostly used for the manufacture of handicrafts. One of the plants in question is the pandan plant, with the passage of time, it is necessary to use fiber from pandan plants so that it can be used for the latest technology. In this study, composites were made using pandan fibers, where for variations of this study, namely 0°, 90° and random. As for the process of making composites using the press method and in coating carbon cloth on composite surfaces using the hand lay up method. In this study, researchers conducted tensile testing based on ASTM D-3039 and for impact testing based on ASTM E-23. The results of this study were for specimens in the best tensile testing was at an angle variation of 90° with an average tensile strength of 29.43 MPa. The highest impact test results are in the 90° variation with an absorbable energy value of 2,622 J and for an impact price value of 0.033 J/mm2.